Pengaruh Modal Kerja dan Likuiditas Terhadap Profitabilitas Pada Perusahaan Kosmetik dan Barang Keperluan Rumah Tangga Yang Terdaftar di Bei Periode 2015-2019 - Della Dwi Marinda; Maulan Irwandi; Aris Munandar (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2021)
This study aims to analyze partially and simultaneously the effect of working capital and liquidity on profitability in cosmetic and household goods companies listed on the Indonesia Stock Exchange for the 2015-2019 period. Data collection techniques using documentation and literature study, amounting to 30 correspondents. This study uses multiple linear regression as an analysis tool. The results of the study partially show that the working capital variable has a negative effect on the profitability variable, while the liquidity variable does not affect the profitability. The conclusion from the results of this study that the coefficient of determination (R2 ) obtained a value of 0.507. This shows that the large contribution of working capital and liquidity variables can explain the profitability of 50.7%, the remaining 43.3% can be influenced by other variables not included in this study.